1951
DOI: 10.1104/pp.26.4.750
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Form of Nitrogen and the Amount of Base Supply on the Organic Acids of Tung Leaves

Abstract: Recent research (10) on the nutrition of the tung plant has demonstrated a close relationship betwen cation uptake and the form of nitrogen supplied. For example, tung seedlings grown with all or part of the nitrogen supplied as the ammonium salt have a lower calcium requirement for optimal growth than do those supplied with only nitrate as the nitrogen source. It has been demonstrated that a close relationship exists in the tung plant between the growth of the tree and the balance of the cations supplied (9).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1959
1959
1974
1974

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Our results do not contradict this finding, for at no time was there a fall in the amount of calcium per leaf during the period of sampling, so long as the leaves remained green. Gilbert et al (1951), using tung leaves, and Rasmussen & Smith (1961), using Valencia-orange leaves, have shown a correlation between the concentration of calcium and that of oxalic acid.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results do not contradict this finding, for at no time was there a fall in the amount of calcium per leaf during the period of sampling, so long as the leaves remained green. Gilbert et al (1951), using tung leaves, and Rasmussen & Smith (1961), using Valencia-orange leaves, have shown a correlation between the concentration of calcium and that of oxalic acid.…”
Section: Discussionmentioning
confidence: 94%
“…Much still remains to be discovered about the relationship between the inorganic and organic constituents, although a few general statements can be made. For example, several workers have found that the content of malic acid or oxalic acid in leaves is related to that of calcium (Gilbert, Shear & Gropp, 1951;Rasmussen & Smith, 1961).…”
mentioning
confidence: 99%
“…Ca moved into leaves that were high in metabolic activity. It moved into young leaves and into those sprayed with growth regulators that in- nutrition synthetized less oxalic acid and required less Ca for its neutralization (14). The failure of solutions of salts of these elements to release Ca when passed through stem sections indicates that they do not act through the exchange mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have dealt with the effect of nutrition on organic acids of leaf and fruit tissues (2,3,5,13). In general, the effects of cations on the organic acids in leaf tissue are rather complex.…”
mentioning
confidence: 99%
“…For example, Cooil (1) found that the higher total acids associated with high K in expanding guayule leaves was largely accounted for by high citric acid levels, whereas in mature leaves high malic acid levels were associated with high Ca levels. In tung, oxalic acid formation is directly related to nitrate and Ca supply (3).…”
mentioning
confidence: 99%